GLOBALIZATION (American Journal of Business Management, Economics and Banking, 2023)
In this article Globalization in the development of the modern world economy is one of the most basic processes and is considered a high stage of internationalization of economic life. International division of labor, international cooperation of production, foreign trade and other international economic relations interaction of national economies as a result of the development of forms connection and interdependence are becoming stronger. Current economy of states without taking into account external factors development cannot be ensured. It is known that the interdependence of countries’ economies is increasing, foreign economic relations with national economies the increase in influence, the active participation of large and small countries in international relations is the internationalization of economic activity. The internationalization of the economy has passed through a number of stages past, the first is international economic cooperation and in this case, the rate of foreign trade is extremely important. Between countries regulatory and legal provision of international economic relations, of reproduction processes across national borders exit is international economic cooperation. International economic integration based on the division of labor merger and mutualization of the economies of the same countries to national economies due to effective development of relations can affect in different forms and levels.[1]